Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification